1990
DOI: 10.1093/ndt/5.10.851
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Methods of Estimating Renal Size in Normal Adults

Abstract: One hundred live related voluntary kidney donors were studied prospectively. During donor nephrectomy the actual kidney bipolar length was measured and compared to the renal bipolar length estimated from abdominal sonogram, abdominal plain X-ray, intravenous pyelogram, and renal angiogram. Ultrasound was found to measure the kidney more accurately (mean difference between estimated size and actual = -3.4 mm +/- SD 6.96), than plain X-ray (mean difference from actual 13mm +/- SD 5.24), IVP (mean difference from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…1994 flowmetry, two noninvasive techniques which give useful information on the transplanted organ [4][5][6], Echography offers a picture of kidney morphology and can be used to obtain precise measures of renal size and volume [7][8][9], The analysis of Doppler spectrum allows a direct evalua tion of the blood supply to the graft, renal blood flow (RBF) [10][11][12] and renal vascular resistances (RVR).…”
Section: Introductionmentioning
confidence: 99%
“…1994 flowmetry, two noninvasive techniques which give useful information on the transplanted organ [4][5][6], Echography offers a picture of kidney morphology and can be used to obtain precise measures of renal size and volume [7][8][9], The analysis of Doppler spectrum allows a direct evalua tion of the blood supply to the graft, renal blood flow (RBF) [10][11][12] and renal vascular resistances (RVR).…”
Section: Introductionmentioning
confidence: 99%
“…In all patients, preoperative intravenous urography (IVU) revealed hydronephrosis at different degrees in the whole of the renal collecting system because of the stones placed in the UPJ and drainage of contrast material through both ureters. The degree of hydronephrosis in the obstructed kidney, diameters of kidneys and thickness of renal parenchyma were assessed with ultrasonography (USG), since USG has previously been shown to determine these parameters more accurately 25,26 . Since no previous examination record was available, the duration of obstruction at the time of color Doppler sonography was recorded according to the patient's clinical history based on the pain.…”
Section: Methodsmentioning
confidence: 99%
“…However, Moel H[22] showed that renal dimensions measured by using sonography were smaller than those obtained by using radiography because no geometric magnification and no osmotic diuresis caused by intravenous contrast occurred in the former study. In another study conducted on donor kidneys,[23] the measurements made by using sonography were more accurate than measurements based on plain radiographs, excretory urograms or renal angiograms.…”
Section: Ultrasound Sonographymentioning
confidence: 99%